Search for a heavy neutral particle decaying into an electron and a muon using 1 fb-1 of ATLAS data - Anduaga, Xabier Sebastián (2011)
A search is presented for a high mass neutral particle that decays directly to the e±μ∓ final state. The data sample was recorded by the ATLAS detector in √ s = 7 TeV pp collisions at the LHC from March to June 2011 and corresponds to an integrated luminosity of 1.07 fb-1. The data are found to be consistent with the Standard Model background. The high e±μ∓ mass region is used to set 95% confidence level upper limits on the production of two possible new physics processes: tau sneutrinos in an R-parity violating supersymmetric model and Z'-like vector bosons in a lepton flavor violating model.